Relatório de estágio técnico profissional supervisionado em medicina veterinária: nutrição, reprodução e sanidade de ruminantes - Boff, Keline (2023)
The Professional Technical Internship (ETP) is an opportunity to improve and put into practice all theoretical knowledge acquired during graduation in Veterinary Medicine. The ETP was carried out in the dairy cattle area at the company Cotrijal, covering the cities of Água Santa and Vila Lângaro, during the period from August 2, 2023 to November 8, 2023, totaling 400 hours, under the academic guidance of Prof. Dr. Maria Isabel Botelho Vieira. Through the ETP it was possible to experience the veterinarian's routine, technical assistance provided to cooperative members, in addition to being in contact with high-quality properties technological and also high efficiency within the dairy activity. Furthermore, it was observed aspects related to the formulation of diets, reproductive management, gestational diagnoses and health protocols. Therefore, this report includes a description of the internship location, the general activities developed and finally, a case report on nutritional management in robotic milking. The relevance of the professional technical internship for the professional and personal maturity, experiencing the development routine on properties, having autonomy to apply in practice the knowledge acquired in theory, discussing improvements and solutions with specialized professionals and enriching the academic’s vision about the future of the profession as a veterinarian.